FAKTOR – FAKTOR YANG MEMPENGARUHI KETIDAKPATUHAN PETUGAS PUSKESMAS DALAM PELAPORAN PENILAIAN KINERJA PUSKESMAS (PKP) DI DINAS KESEHATAN KABUPATEN POSO - Tryfena Fenisia Songgo; Achmad Lukman Hakim; Risa Rerungan (Journal of Innovation Research and Knowledge, 2025)
This research aims to analyze the factors influencing the non-compliance of health center officers in reporting the Health Center Performance Assessment (PKP) at the Poso District Health Office. Using a qualitative method approach, namely through in-depth interviews with selected informants. The analysis was conducted thematically with the help of the Nvivo application used for systematic coding to identify important themes and patterns related to non-compliance. The results show that compliance is influenced by personality, job boredom, task distribution, rewards, work environment, and facilities. Boredom can reduce motivation and discipline, while uneven task distribution causes workload to accumulate on certain staff. Factors such as rewards, team support, and the availability of technological facilities have been proven to strengthen compliance. Therefore, efforts to improve compliance need to be carried out comprehensively through individual coaching and strengthening organizational systems so that PKP reporting is More timely and accurate